KNOWLEDGE OF THE EXTENSION AGENTS IN THE SOUTH GREEN BELT IN KARBALA GOVERNORATE WITH RECOMMENDATION AND ITS RELATIONSHIP TO CONNECT TO SOURCES OF INFORMATION - AL-Bahar, A.H.M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The research aims to determine the level of knowledge of agricultural extension workers in the southern green belt project in the holy city of kerbala in terms of scientific recommendations and its relationship with information resources and to determine the level of their knowledge of the following fields: The basic concepts of project objective trees varieties and their economic viability, the stage of cultivation and services provided which includes plantation irrigation and pests control etc., the technical aspects of their project beside the identification of agricultural knowledge of the workers with the relearnt sources of information red event. To achieve the objective of this research based on the scientific research and the produced extension leaflet in regard to soil and desertification in general and green belt in particular. A knowledge scale was adopted which includes 46 paragraphs distributed on five areas two degrees for each paragraphs were determined so that the scale degree ranged between 0-92 degree. The research included 45 agricultural extension members working in this project which represent 100% from the research community. The data collected through a questionnaire forms distributed through October 2014 results showed that 62.22% of the respondents fall within the category of concentric medium as the result showed 0 positive correlation between the level of knowledge of agricultural extension  workers and communication sources of informations  which were worth 0.28% the researcher recommits the need to arise the efficiency of agricultural extension workers through intensive training by the ministry of agriculture and its institutes in all Iraqi Provinces in general and the governorate of kerbala in particular with the need to develop the department of desertification in the colleges of Agriculture similar to that of Baghdad university to provide specialist in desertification and green belts projects as well as the importance of such projects in solving serious problems of desertification on the environment society and national economy .